Continuous locomotor activity monitoring to assess animal welfare following intracranial surgery in mice - Abdollahi Nejat, Mazyar; Stiedl, Oliver; Smit, August B.; van Kesteren, Ronald E. (Frontiers in Behavioral Neuroscience, 2024)
Locomotor activity can serve as a readout to identify discomfort and pain. Therefore, monitoring locomotor activity following interventions that induce potential discomfort may serve as a reliable method for evaluating animal health, complementing conventional methods such as body weight measurement. In this study, we used the digital ventilated cage (DVC®) system for the assessment of circadian locomotor activity, in addition to body weight monitoring, following intracranial stereotaxic surgery in an Alzheimer’s disease mouse model (C57BL/6J/APPswe/PSEN1dE9). Stereotaxic surgery did not affect the organization of circadian locomotor activity of both 7–8-week-old and 19–21-week-old mice. However, we observed that both young and old mice exhibited a significant decrease in activity during the dark phase. Also, our study shows that changes in locomotor activity exhibit higher sensitivity in detecting alterations indicative of animal health compared to measuring body weight. In contrast to 7–8-week-old mice, where we observed no genotypic differences in locomotor activity, 19–21-week-old APP/PS1 mice showed increased locomotor activity compared to wild-type mice. Furthermore, our analyses revealed that a subset of the 7–8-week-old mice showed increased locomotor activity during the initial peak of the dark phase. One mouse experienced sudden death early in life, possibly due to epileptic seizures. Altogether, our findings affirm continuous activity measurements as used in the DVC® as a highly valuable objective method for post-surgical welfare monitoring. Its discerning capacity not only facilitates circadian locomotor rhythm assessment but also enables the identification of individual aberrant activity patterns, possibly indicative of epileptic seizures.